Cities as Engines of Growth: Evidence from a New Global Sample of Cities - Jones, Patricia; Collier, Paul; Spijkerman, Dewi (Journal of Applied Business and Economics, 2020)
This paper presents the first global analysis of the size and sources of agglomeration economies in the developing world. Using establishment data from more than 12,000 firms in 51 developing countries, we estimate the productivity effects of increased city size, population density, and market potential. To do this, we employ a new measure of city size based on LandScan data—a global dataset that estimates the world’s population at approximately 1 km resolution. We find strong evidence that urban productivity rises with city scale in developing economies although the size of these agglomeration effects are smaller in African cities.